Anti-Inflammatory Efficacy of Curcumin as an Adjunct to Non-Surgical Periodontal Treatment: A Systematic Review and Meta-Analysis - Zhang, Yang; Huang, Lei; Zhang, Jinmei; De Souza Rastelli, Alessandra Nara; Yang, Jingmei; Deng, Dongmei (Frontiers in Pharmacology, 2022)
Objective: Curcumin has been used as an adjunct to non-surgical periodontal treatment. However, the efficacy of curcumin in the periodontal therapy remained controversial. This study aimed to evaluate the anti-inflammatory efficacy of curcumin as an adjunct to non-surgical periodontal treatment (NPT) by systematic review. Methods: Databases including Embase, PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), and ClinicalTrials.gov were searched to identify relevant RCTs on the use of curcumin as an adjunct to NPT for the treatment of periodontal disease from inception to July 21, 2021. Two reviewers independently screened literature, extracted data and assessed the risk of bias of the included studies. Meta-analysis was then performed using Review Manager 5.3 software. Results: A total of 18 RCTs involving 846 patients/sites were included in this meta-analysis. The results of the meta-analysis revealed that as compared to NPT alone, curcumin as an adjunct to NPT resulted in significant reduction in gingival index (GI) at the 1-week (mean differences (MD) = -0.15, 95% confidence intervals (CI) -0.26 to -0.05, P = 0.005), 2-week (MD = -0.51, 95%CI -0.74 to -0.28, P < 0.0001), 3-week (MD = -0.34, 95%CI -0.66 to -0.02, P = 0.03), 4-week (MD = -0.25, 95%CI -0.48 to -0.02, P = 0.04) or 6-week (MD = -0.33, 95%CI -0.58 to -0.08, P = 0.01) follow-ups. Similar significant reductions were also observed for sulcus bleeding index (SBI) at 1, 2, 4, and 12 weeks. However, there were no statistically significant differences in reducing bleeding on probing (BOP) between curcumin as an adjunct and NPT alone at 4, 12, and 24 weeks. Conclusion: Based on the current evidence, curcumin demonstrates anti-inflammatory efficacies in terms of reducing GI and SBI compared with NPT alone. Moreover, curcumin is a natural herbal medicine with few side effects, and it is a good candidate as an adjunct treatment for periodontal disease.